Mi nismo anđeli - Dragojević, Srđan (Yugoslavia : Avala Film Beograd, 1992)
This teenage comedy, virtually the only representative of the genre in Yugoslav cinema, centers around 26-year-old literature student Nikola, an incurable bachelor and hard drinking Belgrade playboy with irresistible charm. The trouble begins when keen high-school graduate Marina accidentally ends up as one of his ”one night stands” and gets pregnant. Though Nikola does not even remember her and declines the very thought of becoming a father, Marina falls deeply in love with him. Seeing that she is determined to have his baby, her best friend plans a series of crazy adventures aimed at persuading Nikola to fall in love with Marina. An additional twist to the movie is brought in by two bizarre side-characters, Devil and Angel who bet about the possible ending of this love venture and constantly reappear throughout the movie, commenting passionately on events. After a series of unsuccessful attempts, Nikola slowly begins to change and eventually agrees to marry Buba, only to suddenly flee to a deserted island. There, without alcohol and girls, he recognises all of his mistakes and after a final test ends with a newborn baby in his hands.
Duration: 01:38:00
Keywords: Fiction films